Job Stress on Quality of Work Life among Agriculture Faculties of Federal Universities in South-West, Nigeria - Adeogun, S.O.; Olatoye, F.O.; Adeogun, A.E.; Likoetla, P. (ADAN JOURNAL OF AGRICULTURE, 2026)
The study was conducted to evaluate the effects of job stress on the quality of work life among the Agriculture Faculties of Federal Universities in South-West Nigeria. This study examined the effects that job stress has on the quality of work life of Federal University Faculty staff in South-West Nigeria. A four-stage sampling procedure was used to select 125 Federal University Faculties. Using a structured questionnaire, data were obtained on respondents’ socio-economic characteristics, job stress, stress coping strategies, and quality of work life. Frequency counts, percentages, mean, standard deviation, Chi-square statistic, and Pearson Product Moment Correlation (r) were used to analyse the data. The results revealed that the respondents' mean age was 43.5 years. Most of the respondents were male (57.8%), married (85.3%), Christians (82.6%), PhD degree holders (70.6%), with a mean year of experience of 14.78 years. University staff were faced with a high level of stress (57.8%) with engaging in strategic planning ( ̅ = 4.22) and meditation or prayer ( ̅ = 4.21) were the coping strategies mostly adopted. Results further revealed that facilities ( ̅ = 4.24), job satisfaction and security ( ̅ = 4.18) were the major factors that influenced the quality of work life. Furthermore, the respondents' work-life quality was high (90.2%). Also, there was a significant relationship (p<0.05) between job stress (r = 0.59) and quality of work life. Also, there was a significant relationship (p<0.05) between stress coping strategies (r = 0.207) and quality of work life. The study concluded that job stress and the coping strategies adopted by staff affect the quality of work life among agricultural staff of Federal Universities in South-west Nigeria. Hence, the study recommended that adequate measures that will focus on the reduction of stress should be established in these institutions to maintain the quality of work life among University Staff. Also, staff should adopt the most effective mechanism that suits them in coping with the stress they face daily.